Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s10020-022-00564-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapeutic neuroprotective effect of verapamil against lipopolysaccharide-induced neuroinflammation in mice through modulation of calcium-dependent genes

Abstract: Background Neuroinflammation is a major mechanism in neurodegenerative diseases such as Alzheimer’s disease (AD), which is a major healthcare problem. Notwithstanding of ample researches figured out possible molecular mechanisms underlying the pathophysiology of AD, there is no definitive therapeutics that aid in neuroprotection. Therefore, searching for new agents and potential targets is a critical demand. We aimed to investigate the neuroprotective effect of verapamil (VRP) against lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Many anti-epileptic drugs are P-gp and BCRP transporter substrates 162 and circadian differences in transporter activity may underlie alterations in the effectiveness of the anti-epileptic drugs. Studies of quinidine, 63 verapamil, 163 and other P-gp substrates 68 (described in detail above) have shown higher levels or improved neuroprotective functions at different circadian times. Mosalam et al 163 also examined the efficacy of verapamil, in reducing lipopolysaccharide-induced neuroinflammation when given at 9 am and 5 pm in mice and found greater brain entry of verapamil and neuroprotection at 9 am .…”
Section: Circadian Rhythms and Brain-targeted Drug Delivery (Chronoth...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many anti-epileptic drugs are P-gp and BCRP transporter substrates 162 and circadian differences in transporter activity may underlie alterations in the effectiveness of the anti-epileptic drugs. Studies of quinidine, 63 verapamil, 163 and other P-gp substrates 68 (described in detail above) have shown higher levels or improved neuroprotective functions at different circadian times. Mosalam et al 163 also examined the efficacy of verapamil, in reducing lipopolysaccharide-induced neuroinflammation when given at 9 am and 5 pm in mice and found greater brain entry of verapamil and neuroprotection at 9 am .…”
Section: Circadian Rhythms and Brain-targeted Drug Delivery (Chronoth...mentioning
confidence: 99%
“…Many anti-epileptic drugs are P-gp and BCRP transporter substrates 162 and circadian differences in transporter activity may underlie alterations in the effectiveness of the anti-epileptic drugs. Studies of quinidine, 63 verapamil, 163 and other P-gp substrates 68 (described in detail above) have shown higher levels or improved…”
Section: Evidence On Brain-targeted Chronotherapy From Animal and Hum...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial impairment is widely recognized as a significant contributor to the pathogenesis of AD [ 53 ]. A growing body of evidence suggested that dysregulation of MMP may occur due to oxidative stress and neuroinflammation [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial impairment is widely recognized as a significant contributor to the pathogenesis of AD [ 53 ]. A growing body of evidence suggested that dysregulation of MMP may occur due to oxidative stress and neuroinflammation [ 53 , 54 ]. Furthermore, the process of excessive phosphorylation of tau protein has been observed to impede mitochondrial transport at the synapse, causing severe oxidative stress [ 55 ].…”
Section: Discussionmentioning
confidence: 99%